Rationale, design and methods for a randomised and controlled trial of the impact of virtual reality games on motor competence, physical activity, and mental health in children with developmental coordination disorder - Straker Leon M; Campbell Amity C; Jensen Lyn M; Metcalf Deborah R; Smith Anne J; Abbott Rebecca A; Pollock Clare M; Piek Jan P (BMC, 2011)
Abstract Background A healthy start to life requires adequate motor development and physical activity participation. Currently 5-15% of children have impaired motor development without any obvious disorder. These children are at greater risk of obesity, musculoskeletal disorders, low social confidence and poor mental health. Traditional electronic game use may impact on motor development and physical activity creating a vicious cycle. However new virtual reality (VR) game interfaces may provide motor experiences that enhance motor development and lead to an increase in motor coordination and better physical activity and mental health outcomes. VR games are beginning to be used for rehabilitation, however there is no reported trial of the impact of these games on motor coordination in children with developmental coordination disorder. Methods This cross-over randomised and controlled trial will examine whether motor coordination is enhanced by access to active electronic games and whether daily activity, attitudes to physical activity and mental health are also enhanced. Thirty children aged 10-12 years with poor motor coordination (≤ 15th percentile) will be recruited and randomised to a balanced ordering of 'no active electronic games' and 'active electronic games'. Each child will participate in both conditions for 16 weeks, and be assessed prior to participation and at the end of each condition. The primary outcome is motor coordination, assessed by kinematic and kinetic motion analysis laboratory measures. Physical activity and sedentary behaviour will be assessed by accelerometry, coordination in daily life by parent report questionnaire and attitudes to physical activity, self-confidence, anxiety and depressed mood will be assessed by self report questionnaire. A sample of 30 will provide a power of > 0.9 for detecting a 5 point difference in motor coordination on the MABC-2 TIS scale (mean 17, sd = 5). Discussion This is the first trial to examine the impact of new virtual reality games on motor coordination in children with developmental coordination disorder. The findings will provide critical information to understand whether these electronic games can be used to have a positive impact on the physical and mental health of these children. Given the importance of adequate motor coordination, physical activity and mental health in childhood, this project can inform interventions which could have a profound impact on the long term health of this group of children. Trial registration Australia and New Zealand Clinical Trials Register (ANZCTR): ACTRN12611000400965